2016
DOI: 10.1111/ppa.12540
|View full text |Cite
|
Sign up to set email alerts
|

Colonization of the vegetative stage of rice plants by the false smut fungus Villosiclava virens, as revealed by a combination of species‐specific detection methods

Abstract: Rice false smut disease caused by the ascomycete fungus Villosiclava virens (Clavicipitaceae) reduces rice yield worldwide. It invades rice panicles and forms dark-green false smut balls composed of thick-walled conidia. Although the infection process during the booting stage is well studied, its infection route before this is unclear. It was hypothesized that the thick-walled conidia in soil penetrate rice roots, and the fungus latently colonizes roots and tiller buds at the vegetative stage. This hypothesis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 20 publications
0
8
1
Order By: Relevance
“…The pathogens could not penetrate the sclerenchyma cell or the endothelial cells of the root, so they could not reach the endodermis, the phloem of the rice root, and could not expand into the stem tissue. This is different from previous reports in which the pathogen grew along the sieve tube of the rice (Ikegami ; Tanaka et al, ). Fan et al reported that U. virens displayed epiphytic characteristics on abiotic and biotic surfaces in the presence of water (Fan et al, ).…”
Section: Resultscontrasting
confidence: 99%
“…The pathogens could not penetrate the sclerenchyma cell or the endothelial cells of the root, so they could not reach the endodermis, the phloem of the rice root, and could not expand into the stem tissue. This is different from previous reports in which the pathogen grew along the sieve tube of the rice (Ikegami ; Tanaka et al, ). Fan et al reported that U. virens displayed epiphytic characteristics on abiotic and biotic surfaces in the presence of water (Fan et al, ).…”
Section: Resultscontrasting
confidence: 99%
“…After the transplanting of rice in paddy fields, chlamydospores attach to the roots and then germinate, with the resulting hyphae invading the intercellular space of the roots (Prakobsub & Ashizawa, 2017). Finally, the hyphae extend toward the tiller buds at the basal portion of the juvenile leaf sheath (Tanaka et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The observation of Chou (1967) showed 26-28°C as a suitable temperature for rice false smut. In the very recent findings, Tanaka et al (2017) revealed that while the pathogen was present in rice plants, the development of the disease depended on meteorological conditions, where under field conditions no infection occurred at average temperature of 28°C and good infection was found at 25°C. The findings of Tanaka et al (2017) clearly support the approach of this study on designating temperature during the smut ball formation period as the key indicator for expressing the disease on a crop.…”
Section: Discussionmentioning
confidence: 99%